Collaborative Nursing Interventions in Geriatric Patients with Adrenal Crisis and Blood Glucose Fluctuations: A Case Report - Amelia, Iftikar Salma; Pebrianti, Sandra; Pahria, Tuti (Universitas Padjadjaran, 2025)
Adrenal crisis is an endocrine emergency condition, with one of its clinical manifestations being hypoglycemia. To date, its management focuses on the administration of corticosteroid therapy primarily hydrocortisone as the first-line treatment alongside glucose administration. This study aims to observe and report blood glucose levels, hemodynamic status, and multidisciplinary collaboration in the administration of corticosteroids, as a collaborative intervention in stabilizing blood glucose. This case study was conducted on a 70 years old geriatric patient who experienced an adrenal crisis due to the sudden discontinuation of long-term steroid therapy without a doctor's prescription. Data were collected over five days through patient interviews, family reports, and medical records. The patient experienced severe hypoglycemia despite receiving parenteral glucose. Following the administration of dexamethasone, the patient's blood glucose levels improved and began to stabilize. Dexamethasone proved effective as an alternative initial therapy for adrenal crisis when hydrocortisone was unavailable or the diagnosis is not yet confirmed. Nurses played a vital role in the early recognition of adrenal crisis signs, monitoring of blood glucose levels and hemodynamic parameters. Education for the family is essential, considering the dependency of geriatric patients on caregivers in managing daily health needs. Multidisciplinary collaborative management and educational support are key to successful care in geriatric patients with adrenal crisis.